Effect of clinical mastitis on lactation curves of Murrah buffaloes - KSHANDAKAR, SHASHANK; VERMA, MED RAM; SINGH, YASH PAL; KUMAR, SANJAY; PAUL, AMRIT KUMAR (The Indian Journal of Animal Sciences, 2018)
India accounts 18.5% of the world milk production and ranked first in milk production. Buffaloes (Bubalus bubalis) produce 54% of total milk production of India. However, mastitis remains the most expensive production disease of the buffaloes. The present study was based on the lactation records of Murrah buffaloes maintained at Cattle and Buffalo Breeding Farm of LPM Section, ICAR-Indian veterinary research institute, Izatnagar over a period of 10 years (2005–2014). The aim of present study was to find best fitted lactation model explaining the lactation behaviour of Murrah buffaloes in healthy and mastitis condition. The data consisted of 80068 daily test day milk yield records of 296 Murrah buffaloes. Different standard lactation curve models such as Ali and Schaeffer (1987), Cobby and Le Du (1978), Sikka (1950), Mitscherlich × Exponential (Rook et al. 1993), Mixed log (Guo and Swalve 1995), Wilmink (1987) and Wood (1967) models were fitted by Proc NLIN Procedure of SAS 9.3. The goodness of fit was judged by the high value of R2 adj and low value of MSPE, AIC and BIC. Durbin-Watson test was used to test autocorrelation and Shapiro-Wilk’s test and Kolmogorov Smirnov test was used to test the normality of the residuals. Based on the analysis of the data Ali and Schaeffer model was the best fitted model to explain the lactation behaviour of the healthy as well as mastitic Murrah buffaloes.